Inhibition of matrix metalloproteinases by HIV-1 integrase strand transfer inhibitors - Foster, Emma G.; Palermo, Nicholas Y.; Liu, Yutong; Edagwa, Benson; Gendelman, Howard E.; Bade, Aditya N. (Frontiers in Toxicology, 2023)
More than fifteen million women with the human immunodeficiency virus type-1 (HIV-1) infection are of childbearing age world-wide. Due to improved and affordable access to antiretroviral therapy (ART), in utero antiretroviral drug (ARV)-exposed children have exceed a million and continues to grow each year. While most recommended ART taken during pregnancy suppresses mother to child viral transmission, the knowledge of drug safety linked to fetal neurodevelopment remains an area of active investigation. For example, few studies have suggested that ARV use can be associated with neural tube defects (NTDs) and most notably with the integrase strand inhibitor (INST) dolutegravir (DTG). After risk benefit assessments, the World Health Organization (WHO) made recommendations for DTG usage as a first and second-line preferred treatment for infected populations including pregnant women and those of childbearing age. Nonetheless, long-term safety concerns remain for fetal health. This has led to a number of recent studies underscoring the need for biomarkers to elucidate potential mechanisms underlying long-term neurodevelopmental adverse events. With this goal in mind, we now report the inhibition of matrix metalloproteinases (MMPs) activities by INSTIs as an ARV class effect. Comprehensive molecular docking testing of the INSTIs, DTG, bictegravir (BIC), and cabotegravir (CAB), against twenty-three human MMPs showed broad-spectrum inhibition. With a metal chelating chemical property, each of the INSTI were shown to bind Zn++ at the MMP’s catalytic domain leading to MMP inhibition but to variable binding energies. These results were validated in myeloid cell culture experiments demonstrating MMP-2 and 9 inhibitions by DTG, BIC and CAB and even at higher degree than doxycycline (DOX). Altogether, these data provide a potential mechanism for how INSTIs could affect fetal neurodevelopment.